2015
DOI: 10.1038/srep07850
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Nanobodies that Block the Enzymatic and Cytotoxic Activities of the Binary Clostridium Difficile Toxin CDT

Abstract: The spore-forming gut bacterium Clostridium difficile is the leading cause of antibiotic-associated diarrhea in hospitalized patients. The major virulence factors are two large glucosylating cytotoxins. Hypervirulent strains (e.g. ribotype 027) with higher morbidity and mortality additionally produce the binary CDT toxin (Clostridium difficile transferase) that ADP-ribosylates actin and induces microtubule-based cell protrusions. Nanobodies are robust single domain antibodies derived from camelid heavy chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 64 publications
(112 reference statements)
0
42
0
1
Order By: Relevance
“…We have generated new VHHs as a tool to identify a region that allosterically regulates the enzymatic activity of UBC6e. VHHs have proven to be particularly useful as reagents for modulating the activity of enzymes [36][37][38] . VHHs have been identified that inhibit 37,39 or augment enzymatic activity 39, 40 , through direct active site binding 37,41 or via allosteric mechanisms 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…We have generated new VHHs as a tool to identify a region that allosterically regulates the enzymatic activity of UBC6e. VHHs have proven to be particularly useful as reagents for modulating the activity of enzymes [36][37][38] . VHHs have been identified that inhibit 37,39 or augment enzymatic activity 39, 40 , through direct active site binding 37,41 or via allosteric mechanisms 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of promising toxinneutralizing murine and humanized monoclonal antibodies (mAbs) are in the pipeline, the emergence of technologies surrounding the generation and expression of toxin-specific camelid heavy chain-only VH domains (VHHs) 3 has opened up new avenues for the rational design and delivery of antitoxin agents (5). VHHs with toxin-neutralizing activity have been described against botulinum neurotoxin (6), Clostridium difficile toxins TcdA and TcdB (7)(8)(9), Shiga toxins (10), ricin (11,12), and anthrax toxin (13). X-ray crystallography of toxin-VHH complexes has provided novel insights into the mechanisms of toxin neutralization (7,14) and single chain antibodies have been successfully delivered into the intracellular compartment of mammalian cells where they can effectively inactivate their targets (15).…”
mentioning
confidence: 99%
“…18, № 6 наноантитела. Эти наноантитела могут быть ис-пользованы в качестве инструментов для ис-следований, диагностики и терапии Clostridium difficile-ассоциированных заболеваний [114].…”
Section: однодоменные антителаunclassified